Lipid Nanocarriers-Enabled Delivery of Antibiotics and Antimicrobial Adjuvants to Overcome Bacterial Biofilms - Anam Ahsan; Nicky Thomas; Timothy J. Barnes; Santhni Subramaniam; Thou Chen Loh; Paul Joyce; Clive A. Prestidge (MDPI AG, 2024)
The opportunistic bacteria growing in biofilms play a decisive role in the pathogenesis of chronic infectious diseases. Biofilm-dwelling bacteria behave differently than planktonic bacteria and are likely to increase resistance and tolerance to antimicrobial therapeutics. Antimicrobial adjuvants have emerged as a promising strategy to combat antimicrobial resistance (AMR) and restore the efficacy of existing antibiotics. A combination of antibiotics and potential antimicrobial adjuvants, (e.g., extracellular polymeric substance (EPS)-degrading enzymes and quorum sensing inhibitors (QSI) can improve the effects of antibiotics and potentially reduce bacterial resistance). In addition, encapsulation of antimicrobials within nanoparticulate systems can improve their stability and their delivery into biofilms. Lipid nanocarriers (LNCs) have been established as having the potential to improve the efficacy of existing antibiotics in combination with antimicrobial adjuvants. Among them, liquid crystal nanoparticles (LCNPs), liposomes, solid lipid nanoparticles (SLNs), and nanostructured lipid carriers (NLCs) are promising due to their superior properties compared to traditional formulations, including their greater biocompatibility, higher drug loading capacity, drug protection from chemical or enzymatic degradation, controlled drug release, targeted delivery, ease of preparation, and scale-up feasibility. This article reviews the recent advances in developing various LNCs to co-deliver some well-studied antimicrobial adjuvants combined with antibiotics from different classes. The efficacy of various combination treatments is compared against bacterial biofilms, and synergistic therapeutics that deserve further investigation are also highlighted. This review identifies promising LNCs for the delivery of combination therapies that are in recent development. It discusses how LNC-enabled co-delivery of antibiotics and adjuvants can advance current clinical antimicrobial treatments, leading to innovative products, enabling the reuse of antibiotics, and providing opportunities for saving millions of lives from bacterial infections.